The Impact Of Service Quality On Customer Satisfaction At BMT Taman Indah, Baitussalam District, Aceh Besar Regency - Hibban, Nafisul; Amanatillah, Dara; Ayumiati, Ayumiati (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
Service quality is an action and effort undertaken by businesses or companies to provide satisfaction to customers. Customer satisfaction or dissatisfaction is the customer's response to the evaluation of perceived discrepancies between prior expectations and the actual performance of the product perceived after its use. The satisfaction levels among consumers tend to differ from one another, and this occurs due to various factors such as age, occupation, income, education, gender, etc. Based on initial observations, the Islamic Cooperative (BMT) often experiences delays in providing services, such as fund disbursement or other transaction processes. This can make customers feel dissatisfied and unappreciated. The purpose of this research is to determine the extent of the influence of service quality on the level of customer satisfaction at BMT Taman Indah in the Baitussalam District. The research employed a field research approach with a quantitative method, distributing questionnaires to 93 respondents. The sample selection technique used the Slovin formula, and data analysis was performed using simple linear regression analysis. The results of this study indicate that in the t-test (partial), service quality has a positive and significant influence on customer satisfaction at BMT Taman Indah in the Baitussalam District.